EVALUATION OF HEMOGRAM, ACUTE PHASE RESPONSE, ACID BASE BALANCE AND BLOOD GAS ANALYSIS IN NEWBORN FOALS INFECTED WITH BABESIOSIS - K. M. Alsaad (Journal of Animal and Plant Sciences, 2014)
The aims of the present work were to evaluate hemogram, acute phase response acid base balance and blood gas analysis in newborn foals infected with Babesiosis. Thirty three newborn foals were infected with Babesia spp. and ten clinically normal foals served as controls. There was a significant reduction in the mean values, TRBc, Hb, PCV in diseased newborn foals infected with Babesiosis and anemia was of Macrocytic hypochromic type. Results also indicated significant increase in total leukocytes count as significant increase in lymphocytes. Infection with Babesia spp. was diagnosed on the basis of Giemsa stained blood smears and was confirmed by competitive c-ELISA testand results showed that out of 33 samples tested (100%) of foals were seropositive for B. equi, whereas no antibodies were detected for B. caballi. Results were also showed significant decrease in blood pH, Pco2, Bicarbonate, Base access and Oxygen saturation percent (So2), However significant increase in Anion gab was found and Titritional metabolic acidosis was indicated. Furthermore significant decrease in haptoglobin and fibrinogen have been encountered in diseased newborns foals. It have been concluded that Babesiosis causes economic loss, therefore all anemic foals born in endemic areas should be screened for Babesia spp.
Keywords: Babesiosis; newborn foals; hemogram; Acute phase response; Acid base balance; Blood gas analysis